PENGARUH PENGGUNAAN METODE PQ4R TERHADAP HASIL BELAJAR MATEMATIKA - Siti Julaeha; Iim Marfua'ah (Universitas Majalengka, 2022)
In the era of globalization in the world of education, it is necessary to consider things in facing the challenges of today's world of education. The world of education is growing as the information age advances sharply. Therefore, education is very important to pay attention to for the development of the nation as an effort to increase human resources who excel in improving the welfare of the nation. One of the cases found in the field is the obstacle for SMK students to master the matrix material. The research method used is experiment. Where will be selected randomly and then compared the learning outcomes of the experimental class with the PQ4R method with the control class with conventional learning using Control Group Design. The research was conducted at a Vocational High School in Bekasi, namely SMK Bina Insan Kamil with 30 students as respondents in the Experiment class and 30 students as respondents in the control class. The sample in this study was taken by cluster random sampling technique. This study gives the result that there is a difference in the average learning outcomes of mathematics between students who are taught using the PQ4R learning method and students who are taught using conventional learning methods. Looking further, it can be said that the results of learning mathematics in students who are taught by the PQ4R learning method are better than the results of students who are taught by conventional learning methods.